Reversible Inactivation of the Higher Order Auditory Cortex during Fear Memory Consolidation Prevents Memory-Related Activity in the Basolateral Amygdala during Remote Memory Retrieval - Cambiaghi, Marco; Renna, Annamaria; Milano, Luisella; Sacchetti, Benedetto (Frontiers in Behavioral Neuroscience, 2017)
Recent findings have shown that the auditory cortex, and specifically the higher order Te2 area, is necessary for the consolidation of long-term fearful memories and that it interacts with the amygdala during the retrieval of long-term fearful memories. Here, we tested whether the reversible blockade of Te2 during memory consolidation may affect the activity changes occuring in the amygdala during the retrieval of fearful memories. To address this issue, we blocked Te2 in a reversible manner during memory consolidation processes. After 4 weeks, we assessed the activity of Te2 and individual nuclei of the amygdala during the retrieval of long-term memories. Rats in which Te2 was inactivated upon memory encoding showed a decreased freezing and failed to show Te2-to-basolateral amygdala synchrony during memory retrieval. In addition, the expression of the immediate early gene zif268 in the lateral, basal and central amygdala nuclei did not show memory-related enhancement. As all sites were intact upon memory retrieval, we propose that the auditory cortex represents a key node in the consolidation of fear memories and it is essential for amygdala nuclei to support memory retrieval process.